2006
DOI: 10.1177/1523422305283075
|View full text |Cite
|
Sign up to set email alerts
|

National Human Resource Development in Transitioning Societies in the Developing World: Brazil

Abstract: The problem and the solution. This article explores and describes Brazil within the transitioning contexts of economic, political, and sociocultural growth and development. Although major components of its economy participate in the global marketplace, significant portions of its population live in poverty, poor health, and illiteracy. Its history includes a colonial past marked by the use of slavery, gross inequalities between races and in educational opportunities, uneven development of the economy, and prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…Along with recent reforms to combat ineffective governance, corruption, public disenfranchisement, and emigration of educated Moroccans, the authors urged HRD professionals and policy makers to promote job creation and increased earnings for the workforce, and collaboration among the government ministries for education, training, and economic development. Similar challenges are discussed by Hasler, Thompson, and Schuler (2006) in their examination of the role of national human resource development (NHRD) in addressing the socioeconomic and political issues in Brazil. Finally, published case studies reported the use of job training and organization development for poverty alleviation and community development in Thailand and Bangalore, India (McLean, Kuo, Budhwani, Yamnill, & Virakul, 2012).…”
Section: Hrd Poverty and The Working Poormentioning
confidence: 96%
“…Along with recent reforms to combat ineffective governance, corruption, public disenfranchisement, and emigration of educated Moroccans, the authors urged HRD professionals and policy makers to promote job creation and increased earnings for the workforce, and collaboration among the government ministries for education, training, and economic development. Similar challenges are discussed by Hasler, Thompson, and Schuler (2006) in their examination of the role of national human resource development (NHRD) in addressing the socioeconomic and political issues in Brazil. Finally, published case studies reported the use of job training and organization development for poverty alleviation and community development in Thailand and Bangalore, India (McLean, Kuo, Budhwani, Yamnill, & Virakul, 2012).…”
Section: Hrd Poverty and The Working Poormentioning
confidence: 96%
“…Brazil's status as a developing country is reflected in its pursuit of socioeconomic and political improvement, as well as, the development of knowledge and skill at the individual and collective levels (Eqbal, 1980). Attentive to the framework constructed by Paprock's (2006) derivation of Harbison and Myers (1964) perspective on development, Hasler, et al, (2006) noted several contrasting conditions such as regional prosperity versus extreme poverty, exemplary universities versus unequal educational opportunities, and significant development investment versus persistent workforce training gaps.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The time in between these periods has shaped Brazil's political perspectives, as wars, coup d'etat's, and military rule have influenced how it governs and the nature of their regional and international relationships. As recognized by Hasler et al (2006) race has influenced the political process through the development of race oriented initiatives and political organizations (Beato, 2004).…”
Section: Politicalmentioning
confidence: 99%
See 2 more Smart Citations